1984
DOI: 10.1002/clc.4960071005
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroquinidine versus disopyramide: Efficacy in patients with chronic stable ventricular ectopy

Abstract: Summary: Dihydroquinidine (DQ) is contained in sub-stantial amounts in quinidine salts, but its direct antiarrhythmic action has not been studied. The efficacy of oral DQ (300 mg t.i.d.) compared to disopyramide (D) (200 mg t.i.d.) was thus investigated using a double-blind crossover placebo-controlled protocol in 12 patients, aged 13 to 67 years, with chronic stable high frequency premature ventricular beats (PVB), defined as > 100 PVB/h during 48-72-h control Holter monitoring. The protocol included three 72… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
1996
1996

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The clinical usefulness of DQ in patients with ventricular arrhythmias, in the absence of ischemic heart disease, has been recently demonstrated in a controlled study in which DQ had a greater suppressive effect on PVB's than disopyramide [5]. Recently L~vy et al [6] have shown the drug to be highly effective in preventing recurrences of ventricular tachycardia in patients with previous myocardial infarction.…”
Section: Comparison Of Dq and Q Effectivenessmentioning
confidence: 99%
“…The clinical usefulness of DQ in patients with ventricular arrhythmias, in the absence of ischemic heart disease, has been recently demonstrated in a controlled study in which DQ had a greater suppressive effect on PVB's than disopyramide [5]. Recently L~vy et al [6] have shown the drug to be highly effective in preventing recurrences of ventricular tachycardia in patients with previous myocardial infarction.…”
Section: Comparison Of Dq and Q Effectivenessmentioning
confidence: 99%